Synthesis of molecular species for supramolecular assembly - Taleb, Nassiba (2011)
This thesis details the synthesis and study of molecular species designed to form supramolecular assemblies, in particular for surface deposition purposes. The first chapter gives a brief introduction to supramolecular chemistry concepts and the basis on which this project is built. The importance of non-covalent bonding interactions to form complex architectures capable of self-assembly is discussed, in particular hydrogen bonds and pi-pi interactions with a series of examples from the literature to illustrate the work that has been accomplished over the past few years in various fields of supramolecular chemistry and nanotechnology in particular. The present project aims at the design, the synthesis and the characterisation of two different groups of compounds, namely p-terphenyl tetracarboxylic acid derivatives and manganese based single molecule magnets. The former are dealt with in the second chapter of the present thesis. The scientific background and the recent results obtained following the surface deposition of p-terphenyl-3,5,3',5'-tetracarboxylic acid are explained and discussed in the introduction. The focus of the research is to design and synthesise similar derivatives, i.e capable of self-assembling to produce similar ordered arrays on surfaces as observed for the parent molecule, but bearing some specific functional groups that are anticipated to either induce a change in the observed assembly process or even impart the molecular functionality upon the assembly. The third chapter of the thesis describes the synthesis and functionalisation of manganese-based single molecule magnets, which are believed to be promising candidates for future applications such as high-density data storage. The crystal structures of some derivatives are discussed and a crystallographic comparative study between the as-synthesised derivatives and literature examples is detailed. In addition, the magnetic properties of selected complexes are discussed and compared. Finally, the results resulting from surface deposition studies that have been carried out in collaboration with the School of Physics and Astronomy at the University of Nottingham are presented in the last section of this chapter.